Framed / 3 / 3. - Korman, Gordon (Swindle, 2010)
Griffin Bing is in big trouble when a Super Bowl ring disappears from his middle school's display case, replaced by Griffin's retainer, and the more he and his friends investigate, the worse his situation becomes.